Tournament of appeals: granting judicial review in Canada - Flemming, Roy B. (UBC Press, 2004)
"Tournament of Appeals investigates the leave to appeal process in Canada and explores how and why certain cases "win" a place on the Court's agenda and others do not. Drawing from systematically collected information on the process, applications, and lawyers. Roy Flemming offers both a qualitative and quantitative explanation of how Canada's justices grant judicial review. This study will draw the attention of lawyers, academics, and students in North America as well as in the Commonwealth or Europe, where the appeals process in the high courts is similar to that of Canada."–BOOK JACKET.